2022
DOI: 10.3991/ijep.v12i1.24407
|View full text |Cite
|
Sign up to set email alerts
|

Online Course Design Using VoiceThread with TPACK Model to Enhance English Speaking Skills for Non-native Learners

Abstract: –Learning English as a foreign language (EFL) and computer technology are two fundamental skills for learners majoring computer science and control engineering not only for the use in academic fields but also for the means of communication worldwide. Among language skills, speaking is a core output element that all learners wish to achieve. This research looked into TPACK (Technological Pedagogical and Content Knowledge) model with an aim to de-sign an online English speaking course for non-English majored lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The findings revealed that, regardless of their confidence level, VoiceThread provides students with a safe, low-anxiety environment to practice listening and speaking. Other studies also confirm that the VoiceThread application can be an assistive tool (Nguyen & Takashi, 2022) that helps learners work independently and improve their productive skills as well as their receptive skills (Munive et al, 2021) and could be beneficial to developing their communicative skills (Utami & Santosa, 2023).…”
Section: Applications As Facilitating Tools To Improve Productive Skillsmentioning
confidence: 76%
See 1 more Smart Citation
“…The findings revealed that, regardless of their confidence level, VoiceThread provides students with a safe, low-anxiety environment to practice listening and speaking. Other studies also confirm that the VoiceThread application can be an assistive tool (Nguyen & Takashi, 2022) that helps learners work independently and improve their productive skills as well as their receptive skills (Munive et al, 2021) and could be beneficial to developing their communicative skills (Utami & Santosa, 2023).…”
Section: Applications As Facilitating Tools To Improve Productive Skillsmentioning
confidence: 76%
“…The same findings were indicated in the Mahmud et al study (2023), which confirmed the positive effect on learners' collaboration and communication skills and their positive perception of using Web 2.0 in a collaborative learning context. Some researchers, Smith and Dobson (2009), Tuyet and Khang (2020), Chang and Windeatt (2021), Nguyen and Takashi (2022), and Andiappan et al (2022), mentioned that teachers who have used Web 2.0 tools in their classroom have noticed that students have a positive attitude towards their use in classroom…”
Section: Web 20 Applications As Motivational Toolsmentioning
confidence: 99%
“…In L2 acquisition, the ability to speak is considered a key skill that needs to be developed [5,9,12]. Speaking is a productive skill that allows language learners to communicate effectively with others and establish meaningful relationships.…”
Section: Oral Communication Skill -Speaking Skillmentioning
confidence: 99%
“…Nevertheless, speaking in English is challenging for most Asian EFL (English as a Foreign Language) learners, as indicated by previous studies of Asian scholars [7,8,9,10]. One significant challenge that non-native learners often face is the limited opportunities to practice and improve their English language skills [5,10]. However, technology has made Using Flipgrid Videos to Enhance Speaking and Presenting in English for Non-Native Learners it possible to overcome this challenge by providing a range of digital tools that can assist in language learning [3,4,11].…”
Section: Introductionmentioning
confidence: 99%
“…As the pace of globalization accelerates in modern society, English teaching is widely regarded as a key factor in opening the door to the global stage [1,2]. In China, English skills have been considered an important criterion for assessing individuals' qualifications, from elementary schools to universities and colleges, and even in the workplace after graduation [3,4]. However, despite the large number of resources invested in English teaching, including teaching equipment, professional faculties, and rich course resources for students, many of them still lack sufficient learning initiative and persistent motivation, which has greatly limited their academic achievements and affected their competitiveness in the workplace [5].…”
Section: Introductionmentioning
confidence: 99%